Optimization Of Social Character Building In The Empowerment Of Islamic Communities In Pringsewu Lampung - Wiwin Windayanti (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Various problems of social phenomena in the last decade tend to lead to a condition of degradation or 'shift' of social morality uncontrollably. If this condition is not considered by all elements of the nation, it will generally have an impact on the process of disorientation, direction and purpose of national life. For this reason, efforts are needed to strengthen social morality from various elements of the nation by developing character education or moral education for the younger generation at various age levels (children, adolescents, and youth) with the need to revitalize and optimize the role of family, school, and community institutions as 3 pillars of education. In fact, students are educated to form characters who will depart and return to society, thus requiring observers of education, including Islamic education, to reflect on the process of community empowerment. This study uses a qualitative approach because researchers want to understand and reveal the problems that are being experienced by the subject of in-depth study. Qualitative research is research that involves the collection of data in a natural environment with the purpose of explaining phenomena that occur in which researchers act as the main instrument. Human resource empowerment involves many aspects, namely mental attitude aspects, behavioral aspects, ability aspects, intellectual aspects, religious aspects, legal aspects, health, etc. All these aspects are two potentials that every individual possesses, which are physical and mental. It cannot be denied that the material aspect is always determined by the spiritual factor, which is the driving force that motivates people. To obtain quality human resources, the most important effort is actually to increase human potential through optimizing social character supported by government programs through educational institutions and community organizations.